An analysis of the enrolment of St. Paul College of Manila for 1970-1977 and an enrolment projection for 1978-1982 - Lapid, Mary Edith (Animo Repository, 1977)
v. 1. This research study is an attempt to analyze the present enrollment of the Collegiate department of St. Paul College of Manila, with the aim in view of projecting the school population of the same college in the next five years, so that the school administrators might make use of it in making a realistic educational planning for the school within the next five years. Specifically, the study sought to answer the following questions: 1) What was the composition of enrollment in the last seven years? 2) What was the trend of enrollment of SPCM in the last seven years per course covered in the study? 3) What will be the effect of limiting freshmen enrollment to 600 to the population of SPCM? 4) What effect has an assumed capacity level of 3000 school population on the freshmen enrollment? In this particular study, the historical-analytical method was used. The data used were the enrollment lists of the different courses involved in the study covering school years 1970-1977. The analysis and interpretation of the data was based on the enrollment data and from the retention rates of enrollment. To determine the enrollment projection, the procedures used consisted of the alpha and beta average retention rates and the moving averages. Based on the findings, recommendations were then presented. v. 2. This work is designed primarily for St. Paul School of Medellin, purely a secondary school. It has been manage by four principals since the start of its operations. Each of the principals did her best and exerted her utmost effort to effect good management. Because of its simple organization, the relations between the administrators and the school personnel are based on trust and confidence. Policies are transmitted verbally. Consequently these policies are remembered inaccurately, if not, totally forgotten. Conflicts and confusion will inevitably arise in any organization, when there is no clear understanding between the school head, the faculty members and other personnel because policies are not written in black and white. Obviously, then, there is a felt need for upgrading the personnel-administrators relations. To insure consistency of action and systematic administration, the writer saw the necessity of providing written guidelines for the school administrator and personnel to gauge efficiency. The interview method was used in the study. The administrator and faculty members as well as retired educators were the ones interviewed. It attempts to define duties and responsibilities of the administrator and school personnel concerned. The following questions raised by the problem were : 1) What policies and practices should be observed and embodied in the manual? 2) What are some concepts that can provide guidelines for administrators to ensure effective and smooth functioning and proper control of the educational set-up? v. 3. Every mid-October, the school holds a musical presentation. The intensive rehearsals start at the beginning of September every Saturday afternoon. Sometimes these rehearsals extend up to late in the evening. On the last Saturday of September the rehearsals finished at half past ten at night. The janitor who was doing his regular cleaning saw smoke coming from the backstage. The stage curtains were burning. With the janitors presence of mind and alertness, the whole academy complex was saved from burning. Everybody was puzzled as to how the fire started. Upon the calling for a principal council to do an interview and investigation of the people possibly involved in the incident and the absence of three girls (participants) in the meeting, the culprits were determined. This is confirmed through the confrontation of the parents with the girls. The next problem of the principal was to whether or not give sanctions to the culprits. The latter part of the paper gives alternative as to how the principal could deal with this dilemma.